Ukranian-Russian Conflict and Its Influence on The Political Speeches: A Discourse Analysis Study 0f The Use of Interpersonal Elements - Arsiyana, Marliza (Lingua Litteria Journal, 2025)
On the 24th February 2022, President Vladimir Putin ordered Russian troops to conduct "Special Military Operations" aimed at the territory of Ukraine. A decision that marked the declaration of war between Russia and Ukraine. This has drawn criticisms, reactions, and condemnations from world leaders. One of them was reaction from President Macron as a leader of one of big countries. As a means to inform and influence society, the President’s speech has a great role in stating the nation’ position related to major global issue. In this regard, it is fascinating to observe the President’s speech deploying interpersonal resources of language about Ukrainian-Russian conflict. Adopting Systemic Functional Linguistics (SFL) framework of interpersonal meaning analysis, this paper highlights the interpersonal elements occurring in President Macron’ Speech. This study analysed French texts which are taken from President Macron’ speech remarks on official website of French President o 24th February 2022 related to Ukrainian-Russian conflict. The analysis was done to reveal the quantitative profiles of different speech functions and Modality element choices made in the texts. Then it goes further in analysing qualitative elaboration of the choices and how these choices affect the overall construction of Ukrainian-Russian Conflict’s language of authority during this time of crisis. The study found that the rhetoric of political leaders mirrors ideologies that align with national, regional, and international frameworks. It also emphasized that grammar in political speech serves beyond syntactic correctness, it plays a crucial role in organizing discourse and conveying ideological messages.